Helping the poor help themselves: Social enterprise and Ireland's peculiar microfinance revolution, c. 1836-1845 - Eoin McLaughlin; Rowena A. Pecchenino (Heriot-Watt University, Department of Accountancy, Economics, and Finance, 2024)
In the decade before the Great Famine, Ireland experienced a boom in microfinance institutions (MFIs). Taking a social enterprise perspective, this paper analyses the institutional context for this boom. It finds evidence linking the boom in MFIs to the development, via the introduction of the poor law in 1838, of a nascent welfare state at the end of a very turbulent period in Irish history. Many contemporary writers saw microfinance as a legal means that could lessen the burden on rate payers by helping the poor help themselves. Econometric analysis at the level of the Poor Law Union confirms the link between MFIs, an Irish solution, and the poor law, a British solution, to Ireland's chronic poverty. The goal of the Irish solution was to address what was perceived to be the cause of poverty, a want of capital, while the British solution addressed the symptoms of poverty but not its root cause.
Keywords: G21; H75; I38; N23; N33; N83; 330; social enterprise; microfinance; inequality; development; Ireland; social enterprise; microfinance; inequality; development; Ireland